2020
DOI: 10.1371/journal.ppat.1009107
|View full text |Cite
|
Sign up to set email alerts
|

Mycolactone toxin induces an inflammatory response by targeting the IL-1β pathway: Mechanistic insight into Buruli ulcer pathophysiology

Abstract: Mycolactone, a lipid-like toxin, is the major virulence factor of Mycobacterium ulcerans, the etiological agent of Buruli ulcer. Its involvement in lesion development has been widely described in early stages of the disease, through its cytotoxic and immunosuppressive activities, but less is known about later stages. Here, we revisit the role of mycolactone in disease outcome and provide the first demonstration of the pro-inflammatory potential of this toxin. We found that the mycolactone-containing mycobacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 66 publications
2
52
0
Order By: Relevance
“…For instance, while many vessels lost both thrombomodulin and vWF, some had lost expression of one marker but not the other. Since it was recently shown that IL-1β is present in BU skin lesions also with variable intensity across biopsy samples [45], we tested the hypothesis that this may add an additional layer of complexity in the in vivo setting. We showed that mycolactone and IL-1β have an additive effect in vitro, suggesting that the variation in marker expression could be caused by the cumulative effect of local mycolactone and IL-1β.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, while many vessels lost both thrombomodulin and vWF, some had lost expression of one marker but not the other. Since it was recently shown that IL-1β is present in BU skin lesions also with variable intensity across biopsy samples [45], we tested the hypothesis that this may add an additional layer of complexity in the in vivo setting. We showed that mycolactone and IL-1β have an additive effect in vitro, suggesting that the variation in marker expression could be caused by the cumulative effect of local mycolactone and IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work showed that IL-1β can be induced by mycolactone-containing microvesicles and is found in M. ulcerans-infected tissues [45]. Since IL-1β has been long-known to repress thrombomodulin expression in endothelial cells by a transcriptional mechanism [46], and also induces vascular permeability [42], we wondered whether the presence of this alarm cytokine might exacerbate the effect of mycolactone on the microvasculature.…”
Section: Il-1β Aggravates Mycolactone-driven Endothelial Dysfunctionmentioning
confidence: 99%
“…However, mycolactone has other cellular activities, facilitating host colonization by this bacillus [8]. At non-cytotoxic concentrations, mycolactone also modulates the immune system, modifying cytokine production and acting on the peripheral nervous system to induce the formation of painless lesions [9][10][11]. This toxin is a distinctive feature of M. ulcerans and plays a key role in its eco-epidemiology and pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Interleukin-1β (IL-1β), a Sec-independent cytokine released through the caspase activated pathway has been shown to be less inhibited by mycolactone, suggesting selective inhibition of inflammatory cytokines in BU disease 3 , 5 , 6 . In fact, a recent study showed that mycolactone induced IL-1β production by murine and human macrophages, possibly through mycolactone-mediated membrane disturbance and the production of reactive oxygen species that trigger NLRP3/1 inflammasome activation, leading to the release of active IL-1β 7 . And, mycolactone does not appear to directly affect neutrophils in BU disease as its toxicity toward neutrophils is observed only in high doses, and absence of neutrophils in BU wounds is mainly attributed to poor neutrophil chemotaxis toward MU 3 , 8 .…”
Section: Introductionmentioning
confidence: 99%